Os impactos da internacionalização e a construção do posicionamento estratégico das empresas brasileiras no cenário globalizado do marketing internacional - Roldão, Jorge Duarte Veiga (2001)
The goal of this work is to identify the im pacts of the Brazilian intemationalization process resumed at the beginning of decade of ninety and the construction of the strategic positioning along ali ofhis historical cycles. This work also objectified identify the dimensions of the competitiveness of a nation and face them with the evolution process of the intemational commerce through centuries, as well as, the effects ofthe phenomenon ofthe globalization and the application of the orientations of the international marketing as guidance for the construction of the positioning strategic of the nations. We conclude that for competitiveness of the nations should be understood and evaluated through the comparative results of your productivity and, consequently, of life quality levei provided to their citizens. The strategies formulations for the intemationalization ofthe nation and her industries can make possible that these objective, in the field of the productivity, be reached or, in case they are badly formulated, can move away them ofthe nation. Therefore, national competitiveness became one of the main preoccupations so much for the govemments who are inserted, as for the ones that are in process of intemational competitive insertion.